Gone with the Wind: Demographic Transitions and Domestic Saving - Eduardo Cavallo; Gabriel Sánchez; Patricio Valenzuela (Inter-American Development Bank (IDB), 2016)
This study explores the relationship between demographic factors and saving rates using a panel dataset covering 110 countries between 1963 and 2012. In line with predictions from theory, this paper finds that lower dependency rates and greater longevity increase domestic saving rates. However, these effects are statistically robust only in Asia. In particular, Latin America, which is a region that has undergone a remarkably similar demographic transition, did not experience the same boost in saving rates as Asia. The paper highlights that the potential dividends arising from a favorable demographic transition are not automatically accrued. This is a sobering message at a time when the demographic tide is shifting in the world.
hdl:11319/7579
Keywords: E21; J10; O16; 330; Demographic dividend; Dependency rates; Saving rates